Vitamin D supplementation and risk of falling: outcomes from the randomized, placebo‐controlled D‐Health Trial. Issue 6 (1st August 2021) - Waterhouse, Mary; Sanguineti, Emma; Baxter, Catherine; Duarte Romero, Briony; McLeod, Donald S.A.; English, Dallas R.; Armstrong, Bruce K.; Ebeling, Peter R.; Hartel, Gunter; Kimlin, Michael G.; O'Connell, Rachel L.; Pham, Hai; et al.
Abstract: Background: Falls cause considerable morbidity and mortality in older people. It is unclear how vitamin D supplementation affects falls risk, particularly when taken at high doses. We sought to determine whether monthly high‐dose vitamin D supplementation reduces risk and incidence of falls. Methods: We used data from the randomized, double‐blind, placebo‐controlled D‐Health Trial conducted in Australia. Between February 2014 and May 2015, 21 315 participants aged 60–84 years were randomized (1:1) to monthly doses of either 60 000 IU of colecalciferol or placebo for a maximum of 5 years. People who reported a history of osteomalacia, sarcoidosis, hyperparathyroidism, hypercalcaemia or kidney stones or who were taking >500 IU/day supplementary vitamin D were ineligible. Each year, we collected blood samples from 450 randomly sampled participants from each trial arm and measured 25‐hydroxyvitamin D [25(OH)D]. Falls, a prespecified tertiary outcome, were ascertained using annual surveys and, for a subset of participants, 3‐month falls diaries. The primary outcome for this analysis was any fall in the month before completing an annual survey. As part of our process to maintain blinding, we used random samples of participants (surveys, n = 16 000; diaries, n = 2400), with equal numbers per group. Participants with no outcome data were excluded. Following an intention‐to‐treat approach, we analysed outcomes using logistic, ordinal and negative binomial regression. Registration: Australian New Zealand Clinical Trials Registry (ACTRN12613000743763); registered 4 July 2013. Results: Mean treatment duration was 4.3 years (standard deviation [SD] = 1.4 years). Mean serum 25(OH)D concentrations during the trial were 114.8 (SD 30.3) nmol/L and 77.5 (SD 25.2) nmol/L in the vitamin D and placebo groups, respectively. Survey and diary analytic sets included 15 416 and 2200 participants, respectively; approximately half were randomized to vitamin D (surveys: 50.1%; diaries: 50.4%). Vitamin D had no effect on falling in the past month (odds ratio [OR] 1.02, 95% confidence interval [CI] 0.95–1.10). There was an interaction with body mass index (BMI) ( P ‐interaction = 0.001); vitamin D increased risk in participants with BMI < 25 kg/m 2 (OR 1.25, 95% CI 1.09–1.43), but there was no effect in those with BMI ≥ 25 kg/m 2 (OR 0.95, 95% CI 0.87–1.04). Analyses of diary data were consistent with these findings. The incidence of hypercalcaemia and kidney stones did not differ between groups. Conclusions: Monthly high‐dose vitamin D supplementation did not reduce risk of falling. A possible increased risk of falling with vitamin D supplementation in people with normal BMI warrants further investigation.